Effect of fibromyalgia syndrome (FMS) on disease activity (DAS28) score in patients with rheumatoid athritis(RA) - Ajeed, Abbas M.; Al-Adhami, Nahida K.; Munshed, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: rheumatoid arthritis (RA) is a systematic autoinmume disease with prevalence of 1% world wild, it is characterized by chronic inflammation of synovial joints, which commonly leads to progressive joints destruction and consequent disability with reduction in quality of life of life.